2015
DOI: 10.1039/c5ra02372f
|View full text |Cite
|
Sign up to set email alerts
|

Colorimetric and optical discrimination of halides by a simple chemosensor

Abstract: A thiophene-based tripodal copper(II) complex has been synthesized as a new colorimetric and optical chemosensor for naked-eye discrimination of halides in acetonitrile and an acetonitrile-water mixture. The binding interactions of the new receptor with several anions were analyzed by UV-Vis titrations, electrospray ionization mass spectrometric (ESI-MS) experiments and density functional theory (DFT) calculations. The results from UV-Vis titrations indicate that the coordinative unsaturated copper(II) complex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 52 publications
1
11
0
Order By: Relevance
“…To shed additional mechanistic insight into the binding motifs of the dinuclear copper complex, we carried out a series of density functional theory (DFT) calculations using the M06L functional. We have specifically chosen the M06L functional for our studies due to its accuracy and widespread use in various organometallic compounds 52 , 53 as well as noncovalent interactions for large systems 54 . An all-electron polarized 6–31 g(d, p) basis set was used for all geometry optimizations, and a larger 6–311 g(d, p) basis was used as a final single-point energy on the optimized geometry.…”
Section: Resultsmentioning
confidence: 99%
“…To shed additional mechanistic insight into the binding motifs of the dinuclear copper complex, we carried out a series of density functional theory (DFT) calculations using the M06L functional. We have specifically chosen the M06L functional for our studies due to its accuracy and widespread use in various organometallic compounds 52 , 53 as well as noncovalent interactions for large systems 54 . An all-electron polarized 6–31 g(d, p) basis set was used for all geometry optimizations, and a larger 6–311 g(d, p) basis was used as a final single-point energy on the optimized geometry.…”
Section: Resultsmentioning
confidence: 99%
“…Time‐ dependent density functional theory (TD‐DFT) : We also performed TD‐DFT calculations to understand the color developed for the fluoride complex during the colorimetric studies. We previously showed that a complete exchange at asymptotic distances is essential to predict excitations in anion complexes . Figure shows the absorption spectra for the free receptor 1 , [ 1 (F)] − and [ 1 (F) 2 ] 2− calculated for the lowest 10 excited states in DMSO solvent.…”
Section: Resultsmentioning
confidence: 99%
“…Recently P. Thordarson et al and J. Jurczak et al have reported that Job plot method for supramolecular complexes need to be used with care . Therefore, to find out the validity of our experimental results for stoichiometry determination for the complexes formed, we used mass spectrometric analysis in the positive mode using ESI‐technique for the complexes (Figure S11) . Compounds R1 and R2 showed a 1:1 stoichiometry with all the tested anions.…”
Section: Anion Binding Studiesmentioning
confidence: 99%